O ensino de geografia no Brasil e a influência neoliberal nos programas de formação docente no século XXI - Rocha, Bianca de Souza (2022)
The content taught by the teacher in the classroom does not correspond only to the surveys, data, contextualizations, and pedagogical explanations of their area of study, but also to a series of factors that go through the essence of their subject basis. The teacher transposes into their class complexities and experiences based on their formation process as a basic education student and college education student as well, and it is important to emphasize that throughout their entire formation process, there were meticulous actions that shaped and led them to reproduce certain behaviors that add up to the teaching and learning process. In order to elucidate such questions, the main purpose of this dissertation is to understand how neoliberalism can influence the teacher's education through teacher education programs in the 21st century, specifically the Institutional Program of Scholarship Initiation to Teaching - PIBID (Programa Institucional de Bolsas de Iniciação à Docência) and the Pedagogical Residency - RP (Residência Pedagógica), and how Geography, intrinsic to the construction of spatialities, can help in this process. For the search and understanding of such analysis, it becomes necessary to carry out a study on how the State figure may be allied to the capitalist production mode and entrust the school with the role of forming individuals adapted to this production mode. This initial discussion and analysis will be held in the first chapter of this work. The second chapter seeks to analyze which principles and precepts characterize the capitalism phase we are living in, neoliberalism. After all, this study will allow us to understand how the teacher education programs are inserted in a structural base that molds individuals to produce a labor force adapted to the conditions of the imposed system. The third chapter conducts an analysis of the teacher education programs PIBID and RP to reveal how they are tied to the whole process of neoliberal influence. Subsequently, possible paths are presented considering the discussions raised.